Efficacy and safety of mesenchymal stromal cells in preclinical models of acute lung injury: a systematic review protocol - Lalu, Manoj M; Moher, David; Marshall, John; Fergusson, Dean; Mei, Shirley H; Macleod, Malcolm; Griffin, Gilly; Turgeon, Alexis F; Rudnicki, Michael; Fishman, Jason; Avey, Marc T; Skidmore, Becky; et al. (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Acute respiratory distress syndrome (ARDS) in humans is caused by an unchecked proinflammatory response that results in diffuse and severe lung injury, and it is associated with a mortality rate of 35 to 45%. Mesenchymal stromal cells (MSCs; ‘adult stem cells’) could represent a promising new therapy for this syndrome, since preclinical evidence suggests that MSCs may ameliorate lung injury. Prior to a human clinical trial, our aim is to conduct a systematic review to compare the efficacy and safety of MSC therapy versus controls in preclinical models of acute lung injury that mimic some aspects of the human ARDS. Methods/Design We will include comparative preclinical studies (randomized and non-randomized) of acute lung injury in which MSCs were administered and outcomes compared to animals given a vehicle control. The primary outcome will be death. Secondary outcomes will include the four key features of preclinical acute lung injury as defined by the American Thoracic Society consensus conference (histologic evidence of lung injury, altered alveolar capillary barrier, lung inflammatory response, and physiological dysfunction) and pathogen clearance for acute lung injury models that are caused by infection. Electronic searches of MEDLINE, Embase, BIOSIS Previews, and Web of Science will be constructed and reviewed by the Peer Review of Electronic Search Strategies (PRESS) process. Search results will be screened independently and in duplicate. Data from eligible studies will be extracted, pooled, and analyzed using random effects models. Risk of bias will be assessed using the Cochrane risk of bias tool, and individual study reporting will be assessed according to the Animal Research: Reporting of In Vivo Experiments (ARRIVE) guidelines. Discussion The results of this systematic review will comprehensively summarize the safety and efficacy of MSC therapy in preclinical models of acute lung injury. Our results will help translational scientists and clinical trialists to determine whether sufficient evidence exists to perform a human clinical trial. These results may also guide future acute lung injury preclinical and clinical research.